Revealing the mechanisms of the bioactive ingredients accumulation in Polygonatum cyrtonema by multiomics analyses - Xue, Ting; Zhao, Miaohua; Chen, Jing; Chen, Youqiang; Zhang, Chuanhai; Li, Baoyin (Frontiers in Plant Science, 2022)
Polygonatum cyrtonema is a medicinal and edible herb rich in polysaccharides, steroidal saponins, and flavonoids that has been widely used as a food, vegetable, and medicine over the years. Although previous studies have preliminarily explored the metabolic and transcriptional regulatory mechanisms of the main secondary metabolites in P. cyrtonema, the complex mechanism of microRNA (miRNA)-mediated posttranscriptional regulation remains unclear. Metabolome analysis showed that iso-ophiopogonanone B, (25S)-pratioside D1, disporopsin, and isodiosgenin-Glc-Glc, which are associated with intermediates in the flavonoids and saponins pathways, were significantly upregulated in the stem and leaf compared with the rhizome, and most saccharides, including arabinose, cellobiose, maltotetraose, and panose, showed the opposite trend, suggesting that they may contribute to the formation and accumulation of the main active ingredients in P. cyrtonema. We found that 4-hydroxymandelonitrile have a relatively good inhibitory effect on α-glucosidase, indicating that it may play a role in hypoglycemic functions. Transcriptome and weighted gene coexpression network analysis (WGCNA) were combined to reveal several candidate genes involved in the accumulation of polysaccharides, saponins, and flavonoids, including PcSQLE, PcCYP71A1, PcSUS, PcFK, and PcMYB102. Integrated analyses of miRNAs and messengerRNAs (mRNAs) showed that novel_miR14, novel_miR49, novel_miR75, and aof_miR164 were negatively correlated with alpha-linolenic acid metabolism and the mitogen activated protein kinase (MAPK) signaling pathway, including PcAOS, PcSPLA2, PcFRK1, and PcDELLA, indicating that these miRNAs may coordinately regulate the biosynthesis of other secondary metabolites in P. cyrtonema. These findings will facilitate in-depth research on the functions of these miRNAs and mRNAs related to the main active substances for pathological and biological regulation, which will be beneficial to provide theoretical guidance for the molecular breeding of P. cyrtonema.